If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3(3 + -4C) = 7 + (7c + -4) (3 * 3 + -4C * 3) = 7 + (7c + -4) (9 + -12C) = 7 + (7c + -4) Reorder the terms: 9 + -12C = 7 + (-4 + 7c) Remove parenthesis around (-4 + 7c) 9 + -12C = 7 + -4 + 7c Combine like terms: 7 + -4 = 3 9 + -12C = 3 + 7c Solving 9 + -12C = 3 + 7c Solving for variable 'C'. Move all terms containing C to the left, all other terms to the right. Add '-9' to each side of the equation. 9 + -9 + -12C = 3 + -9 + 7c Combine like terms: 9 + -9 = 0 0 + -12C = 3 + -9 + 7c -12C = 3 + -9 + 7c Combine like terms: 3 + -9 = -6 -12C = -6 + 7c Divide each side by '-12'. C = 0.5 + -0.5833333333c Simplifying C = 0.5 + -0.5833333333c
| u^3=14u^2+32 | | 12+4c=19 | | K=912+6(140+63-58) | | (6x+4)+2=7 | | 6x+5(4x-2)=10 | | (5x+6)=4 | | 3/4(2y-8) | | (4/9)^(3/2) | | a+0+y+s+e=s*0 | | 0=8ln(6-0.2x) | | (2x+5)(6x-1)=210 | | 4x^2-6x-700=0 | | k(X^2+1)=2Kx-1 | | 2x-55=125 | | 5p-2p=-6p | | 2n-1=3m | | 2x+2y=58 | | a*e-4*s=y*4 | | 6x+2y=106 | | [5X+6]=4 | | (36x^4y^2)^1/2 | | 6.28r+r=64 | | -3x+17= | | 5n^2-8=6n | | 3/8(16y-8)=9-5(y-2) | | 5/32 | | x*y=143 | | 2u^2-4u-5=(u-4) | | (x+4)=8 | | x/4-1.3=-0.05 | | 3cos(2x)=2sin^2*2x | | 3(d+6)= |